Competition in Search Markets with Naive Consumers - Tobias Gamp; Daniel Krähmer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We study the interplay between quality provision and consumer search in a search market where firms may design products of inferior quality to promote them to naive consumers who fail to fully understand product characteristics. We derive an equilibrium in which both superior and inferior quality is offered and show that as search frictions vanish, the share of firms offering superior goods in the market goes to zero. The presence of inferior products harms sophisticated consumers, as it forces them to search longer to find a superior product. We argue that policy interventions that reduce search frictions such as the standardization of price and package formats may harm welfare. In contrast, reducing the number of naive consumers through transparency policies and education campaigns as well as a minimum quality standard can improve welfare.
Keywords: D18; D21; D43; D83; 330; inferior products; competition; naivete; consumer search